Are the T/C polymorphism of the CYP17 gene and the tetranucleotide repeat (TTTA) polymorphism of the CYP19 gene genetic markers for premature coronary artery disease in Caucasians? - Letonja, M; Peterlin, B; Bregar, D; Petrovic, D (Folia biologica, 2005)
Gender differences in CAD have been clearly documented, and sex hormones have been recognized to influence the risk of CAD. The cytochrome P450c17alpha gene (CYP17) and the CYP19 gene influence concentrations of sex hormones. In this cross-sectional association study we tested the hypothesis whether the T/C polymorphism of the CYP17 gene and the tetranucleotide repeat (TTTA) polymorphism of the CYP19 gene are genetic markers for CAD in Caucasians. The TT genotype of the CYP17 gene polymorphism was not associated with premature CAD in men and women combined (OR 0.9; 95% CI = 0.6-1.4; P = 0.7), in men only (OR 1; 95% CI = 0.6-1.8; P = 0.7), and in women only (OR 0.8; 95% CI = 0.5-1.4; P = 0.4). The tetranucleotide repeat (TTTA) CYP19 gene polymorphism was not associated with premature CAD. Moreover, the genotypes containing the longer alleles (A6 or A7) were not associated with a lower incidence of CAD, and the genotypes containing the shorter alleles (A1 or A2) were not over-represented in the CAD patients. We may conclude that in Caucasian subjects neither the T/C CYP17 gene polymorphism nor the tetranucleotide repeat (TTTA) polymorphism of the CYP19 gene contributes to the genetic susceptibility to CAD, therefore they may not be used as genetic markers for CAD risk assessment.
Keywords: lidé středního věku; mikrosatelitní repetice; Case-Control Studies; genetické markery; Genetic Markers; Microsatellite Repeats; Male; aromatasa; Polymorphism, Genetic; steroid-17-alfa-hydroxylasa; alely; studie případů a kontrol; lidé; nemoci koronárních tepen; genotyp; běloši; Coronary Artery Disease; ženské pohlaví; Aromatase; věk při počátku nemoci; Age of Onset; polymorfismus genetický; Alleles; mužské pohlaví; Steroid 17-alpha-Hydroxylase; White People; Middle Aged; Humans; Genotype; Female